2020
DOI: 10.1111/cyt.12804
|View full text |Cite
|
Sign up to set email alerts
|

Rates of Thy 1‐non‐diagnostic thyroid fine needle aspiration using the UK Royal College of Pathologists Thy Terminology. A systematic review of the literature comparing patients who undergo rapid on‐site evaluation and those who do not

Abstract: Introduction: The UK Royal College of Pathologists (RCPath) Thy terminology is an internationally recognised system for reporting thyroid fine needle aspiration. The terminology has been used throughout the UK and Ireland, in some parts of Italy and Switzerland, and elsewhere in the world. There is no systematic review of the literature specifically addressing the use of the non-diagnostic for cytological diagnosis-Thy1/Thy 1c category in the UK RCPath terminology. Methods: A comprehensive literature search of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 37 publications
2
4
0
Order By: Relevance
“…The inadequacy of aspirates has been reported in numerous studies varying from 0.1% to 29%, for various sites and methods [3, 5, 14-24]. Our overall inadequacy rate varied from 3.4% to 9% which is comparable with other large studies.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The inadequacy of aspirates has been reported in numerous studies varying from 0.1% to 29%, for various sites and methods [3, 5, 14-24]. Our overall inadequacy rate varied from 3.4% to 9% which is comparable with other large studies.…”
Section: Discussionsupporting
confidence: 83%
“…Bellivicine et al [15] also reported similar findings in their study. This is further corroborated in a systemic review of literature on Thy1 (non-diagnostic thyroid aspirate) category published by Poller et al [14] in 2020, the inadequacy rates were 13.4% overall, and on stratification with ROSE and without ROSE showed 6% and 18.5% inadequacy, respectively.…”
Section: Discussionsupporting
confidence: 66%
“…A systematic review published earlier this year 14 regarding sites using the UK Royal College of Pathology reporting system found a non-diagnostic, i.e . Thy1, cytology rate ranging from 3.0 to 43.3%.…”
Section: Introductionmentioning
confidence: 99%
“…Although this suggests a need to review regional aspiration practice, a recent review of literature using the RCPath terminology reported Thy1 rates to range from 7.9%‐43.3% 25 . ROSE appears to lower Thy1 rates 25,26 . While the introduction of ROSE would therefore be desirable in our setting, implementation has not been practical due to the number of sites that we serve, with other mitigating factors including lack of space in radiology departments and time constraints with ultrasound lists.…”
Section: Discussionmentioning
confidence: 97%
“…Our Thy1 rate is also high (25%). Although this suggests a need to review regional aspiration practice, a recent review of literature using the RCPath terminology reported Thy1 rates to range from 7.9%‐43.3% 25 . ROSE appears to lower Thy1 rates 25,26 .…”
Section: Discussionmentioning
confidence: 99%